MOVE ANALYSIS OF UNDERGRADUATE THESES AND UNDERGRADUATE STUDENTS' PUBLISHED RESEARCH ARTICLES ABSTRACTS - Annisa Rizkyanti Gustina, - (2020)
Study regarding the rhetorical moves in abstracts of undergraduate theses and undergraduate student's published researcher articles are still understudied. Abstract is the essential part of a scientific paper. A well-written abstract will surely contribute to gain readers' attention effectively. The abstract itself should be informative in order to obtain its essential role. This study aims to examine how the rhetorical moves are applied and to investigate the linguistic features included in the abstract section. It involved a total of 150 science abstracts, 75 abstracts from undergraduate theses and 75 abstracts from undergraduate students' published research articles, from various sources that were randomly selected and assigned for analysis. To validate the data, the author's name of each abstract was verified by examining FORLAP RISTEKDITI site. This study used Hyland's (2000) model as the guideline to conduct the analysis. Antmover was used as the instrument of this study to analyze the moves and steps. The results revealed that both data groups showed some similarities and differences in the realization of rhetorical moves and linguistic features. Using more data to get more comprehensive results is recommended.